Sosialisasi Strategi Kebijakan Perencanaan Wisata Pesisir Berkelanjutan Tanjung Bira dan Lemo-lemo di Dinas Pariwisata, Pemuda dan Olahraga Kab. Bulukumba - Ali, Mukti; Rasyid, Abdul Rachman; Arifin, Mimi; Akil, Arifuddin; Wunas, Shirly; -, Ihsan; Natalia, Venny Veronica; Osman, Wiwik Wahidah; Ekawati, Sri Aliah; Patandianan, Marly Valenti; Sastrawati, Isfa; Dewi, Yashinta Kumala; Wahyuni, Sri; Irfan, Muhammad; Lakatupa, Gafar; Muh Asfan Mujahid, Laode; -, Irwan; Yanti, Suci Anugrah; Mandasari Andi Munawarah Abduh, Jayanti Mandasari Andi Munawarah Abduh; Sagita Alfadin Nur, Dewa (JURNAL TEPAT : Teknologi Terapan untuk Pengabdian Masyarakat, 2024)
Bulukumba Regency is one of the regencies that offers diverse natural and cultural potential. The beauty of the beach panorama is one of the attractions in Bulukumba Regency, including located in the Tanjung Bira Beach Area to Lemo-Lemo Beach. The great potential tourism must continue to be preserved and sustainable. Sustainable coastal tourism planning is a concept that emphasizes environmental, economic and social/cultural aspects. Sustainable tourism planning in Bulukumba Regency, especially in the Tanjung Bira and Lemo-lemo tourism areas, must be supported by stakeholders including the Tourism, Youth and Sports Office. The purpose of the implementation of this activity is to provide strategies or directions in ensuring the sustainability of the Tanjung Bira and Lemo-lemo tourist areas with the concept of sustainable coastal tourism planning. The targets of this activity were the Head, Secretary, Staff at the Tourism, Youth and Sports Office as tourism policy makers in Bulukumba Regency. Evaluation was carried out before and after the activity to measure the achievement of the activity by identifying stakeholder knowledge about sustainable coastal tourism planning policies. Activities were carried out through socialization and explanation of research results and policy directions that can be carried out in ensuring the sustainability of tourism in Tanjung Bira and Lemo-lemo, Bulukumba Regency accompanied by visualization in October 2024. The results showed that 50% did not know about sustainable coastal tourism policies, 6.3% answered undecided and 43.8% already knew. After socialization, the results showed that 87.5% already knew and 12.5% still did not understand this policy